Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.11591/ijeecs.v23.i2.pp1128-1136
|View full text |Cite
|
Sign up to set email alerts
|

Face recognition using enhancement discrete wavelet transform based on MATLAB

Abstract: <p>In this work, it was proposed to compress the color image after de-noise by proposing a coding for the discrete transport of new wavelets called discrete chebysheve wavelet transduction (DCHWT) and linking it to a neural network that relies on the convolutional neural network to compress the color image. The aim of this work is to find an effective method for face recognition, which is to raise the noise and compress the image in convolutional neural networks to remove the noise that caused the image … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Genetic diseases like diabetes, lung diseases, bald head, and cancer may come for the person having similar facial features or structure of the body. Genetic rare diseases may be predicted for the person having same facial features within the family [4,5]. The study found that 8% of people had a hereditary condition, and the majority of them have comparable face traits.…”
Section: Introductionmentioning
confidence: 96%
“…Genetic diseases like diabetes, lung diseases, bald head, and cancer may come for the person having similar facial features or structure of the body. Genetic rare diseases may be predicted for the person having same facial features within the family [4,5]. The study found that 8% of people had a hereditary condition, and the majority of them have comparable face traits.…”
Section: Introductionmentioning
confidence: 96%
“…This paper was organized first, initializing the new discrete wavelet transformations derived from orthogonal aqueous polynomials in previous works that proved their worth in image processing and proving their mathematical aspects discrete laguerre wavelet transform (DLWT) [30]- [36]. Secondly, training the neural network AlexNet.…”
Section: Introductionmentioning
confidence: 99%
“…Reserch from [20], [21] it produces two matrices after factoring low and upper matrix (LU) to be the principal diameter of 1. Solving this problem, the benefits of which are summarized in authentication data and copyright protection, so that the process is in two stages, is to hide the watermark information and restore it [22]- [24].…”
Section: Introductionmentioning
confidence: 99%